Redefining Women’s Roles through Islamic Feminism on the “Bener Gitu?” Channel - Mumtaz Fikri Danasti; Roma Ulinnuha (Academia Open, 2025)
General Background: The role of women in society and Islam has long been a subject of debate, especially in the digital era where online media shape religious and gender discourse. Specific Background: The YouTube channel “Bener Gitu?”, initiated by the Indika Foundation, represents a form of digital da’wah that redefines women’s roles in social and religious contexts through accessible, youth-oriented audio-visual narratives. Knowledge Gap: Despite the rise of digital religious communication, limited research has examined how digital platforms reconstruct women’s social and religious identities from an Islamic feminist perspective. Aims: This study aims to analyze the reconception of women’s roles in the “Bener Gitu?” channel using a qualitative netnographic method with Asghar Ali Engineer’s Islamic Feminism framework. Results: The findings reveal four major reconceptualizations: shared domestic responsibilities between men and women, women’s right to participate in public life, monogamy as the ideal marital form, and individual moral accountability for women. Novelty: The research bridges digital da’wah studies with Islamic feminist theory, presenting a new understanding of how online media serve as agents of gender equality. Implications: This study highlights the potential of digital platforms to foster inclusive Islamic narratives that promote justice, equality, and social transformation in the modern Muslim community. Highlights: Reinterprets women’s roles through Islamic feminist perspectives. Highlights digital media as a tool for inclusive religious discourse. Promotes equality in domestic, public, and moral responsibilities. Keywords: Women’s Role, Digital Da’wah, Islamic Feminism, YouTube Analysis, Gender Equality